first survey of composition on meiofaunal species in the artificial lake on São Francisco river - Pereira, Natan Silva; Nogueira, Eliane Maria de Souza; Carvalho, Eudes Anjos de; Cunha, Adriana (Revista Nordestina de Zoologia, 2012)
Meiofauna from different sedimentary environments has been widely studied, since investigations about its ecology, until its potential use regarding to anthropic action. Aiming to provide new knowledge about the freshwater meiofauna in Brazil, samples were collected monthly (during the rainy and dry season) to investigate the composition and the spatial-temporal distribution of meiofauna present in a punctual area the Upper San Francisco River. At the level of large groups, the meiofauna taxa were represented by: Turbellaria, Oligochaeta, Tradigrada, Acarina, Ostracoda, Copepoda, Insecta, Nematoda, Rotifera. Nematoda and Oligochaeta stood out as very frequent, Rotifera and Acarina, as frequent, Copepoda less frequent and Turbellaria, Tardigrada, insect larvae and Ostracoda were considered sporadic. Nematodes and oligochaetes together accounted for 79.56% of those examined. The dominance of these two groups has been widely appointed in the literature and they are considered the most notable among the freshwater meiofauna. Diversity index of Shannon-Wiener and Simpson pointed to the dominance of one group in the rainy season, expressed by the high density of Oligochaeta, and in the dry season there was a greater diversity, with a more homogeneous distribution of meiofauna taxa.